Preparation of a novel asymmetric wettable chitosan-based sponge and its role in promoting chronic wound healing. (1st January 2020) - Xia, Guixue; Zhai, Dongqing; Sun, Yue; Hou, Lin; Guo, Xiaofan; Wang, Lixia; Li, Zhijian; Wang, Feng
Highlights: The asymmetric wettable CS-based sponge was successfully prepared. The addition of TMC NPs increased the antibacterial activity of the CS sponge. The composite sponge had hydrophobic outer surface and hydrophilic inner surface. The composite sponge had a better capacity of water retention and waterproof. The composite sponge could effectively prevent wound infection. Abstract: Cutaneous chronic wounds are characterized by an impaired wound healing which may lead to infection. To surmount this problem, a novel quaternary ammonium chitosan nanoparticles (TMC NPs)/chitosan (CS)composite sponge with asymmetric wettability surfaces was successfully prepared. The optimum concentrations of TMC NPs and CS were 0.2 mg/mL and 2.0%, respectively. The incorporated TMC NPs could improve the antibacterial activity of the CS sponge. Asymmetric modification enables the CS sponge to have hydrophobic outer surface and hydrophilic inner surface. The hydrophobic surface of the sponge shows waterproof and anti-adhesion contaminant properties, whereas the hydrophilic surface preserves water-absorbing capability and efficiently inhibits the growth of bacteria. More importantly, in vivo chronic wound healing model evaluation reveals that TMC NPs/CS composite sponge promotes the wound healing and accelerates re-epithelialization and angiogenesis. And in vivo anti-infection test shows the TMC NPs/CS composite sponge could effectively prevent wound infection. These findings demonstrate that TMC NPs/CS composite sponge is a promising dressing material for chronic wounds.